Coding metasurface for diffusion‐like scattering in multiple directions based on Pancharatnam–Berry phase. Issue 11 (22nd September 2022) - Feng, Maochang; Li, Xuejian; Chen, Xiaoli; Liu, Zhewei; Li, Yongfeng; Zhang, Jieqiu; Zheng, Qiqi; Wang, Jiafu; Ma, Hua; Qu, Shaobo
Abstract: Diffusion‐like scattering along multiple directions based on coding metasurface (CM) is proposed for both mono‐static and bi‐static radar cross section (RCS) reduction in this work. Different from the previous CMs achieving diffusion‐like scattering only in one direction, the proposed CMs can realize diffusion‐like scattering along multiple directions via designing the phase spatial distributions of the consisted coding elements. The multiple diffusion‐like scattering CMs were designed by using the co‐polarization reflection resonators under circularly polarized wave incidence based on Pancharatnam–Berry (PB) phase. By elaborately arranging the phase spatial distribution of coding elements, two, three, and four beams of diffusion‐like scattering were realized. The bi‐static RCS reduction was improved with increasing number of the backward diffusion‐like scattering beams. The measured results agree well with the simulations, and both demonstrated the excellent performance on mono‐static and bi‐static RCS reduction. Our strategy can help realize stealth applications under bi‐static detections. Abstract : Diffusion‐like scattering along multiple directions based on coding metasurface (CM) is proposed for both mono‐static and bi‐static radar cross section (RCS) reduction in this work. Different from the previous CMs achieving diffusion‐like scattering only in one direction, the proposed CMs can realize diffusion‐like scattering along multiple directions. This strategy can help realize stealth applications under bi‐static detections.